2010
DOI: 10.1007/s00464-010-1092-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized clinical trial comparing lightweight mesh and heavyweight polypropylene mesh in endoscopic totally extraperitoneal groin hernia repair

Abstract: Lightweight meshes appear to have advantages in terms of lesser pain and early return to normal activity. However, more patients had hernia recurrence with lightweight meshes, especially for larger hernias. We surmise that the lightweight meshes have greater tendency to get displaced from their intended position during desufflation at the conclusion of endoscopic TEP repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 30 publications
4
65
2
Order By: Relevance
“…In the present study, chronic relevant pain, according to the classification published by Loos et al [30] present 3 months post-operatively, was reported by 2.0 % of patients after lightweight mesh and 0.9 % of patients after heavyweight mesh use. A comparable study of Chowbey et al [21] showed similar results, reporting moderate to severe pain in 2.1 % patients after lightweight mesh and 1.9 % after heavyweight mesh.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In the present study, chronic relevant pain, according to the classification published by Loos et al [30] present 3 months post-operatively, was reported by 2.0 % of patients after lightweight mesh and 0.9 % of patients after heavyweight mesh use. A comparable study of Chowbey et al [21] showed similar results, reporting moderate to severe pain in 2.1 % patients after lightweight mesh and 1.9 % after heavyweight mesh.…”
Section: Discussionsupporting
confidence: 68%
“…There are only two RCT's comparing lightweight and heavyweight meshes in endoscopic repair with large sample sizes and at least a follow-up of 3 months [20,21]. Both studies showed slight benefits with lightweight meshes during the early post-operative period, regarding chronic pain and impairment of physical activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 It was found the incidence of chronic groin pain at 3.7% in lightweight poylpropylene mesh and 7.1% in heavyweight polypropylene mesh. 28 Authors have reported pain scores in patients receiving lightweight polypropylene mesh were consistently lower than the control group receiving heavyweight polypropylene mesh over a follow up of 1 year. 29 The pain following TEP/TAPP repairs is most commonly somatic which differs from the pain seen after open repairs, which is usually neuropathic.…”
Section: Discussionmentioning
confidence: 99%
“…At least one study demonstrated higher rates of shrinkage for large-pore lightweight mesh compared with small-pore heavyweight meshes (83). Some studies have suggested that large-pore lightweight meshes result in superior tissue integration (84), better elasticity (85) and a lower incidence of pain (86), while other studies report a higher recurrence rate for largepore lightweight mesh in laparoscopically repaired groin hernias, especially in larger hernias (87).…”
Section: Figure 3) a To C The Difference Between Stiffness Elasticitmentioning
confidence: 99%